The Eccentric Phase in Unilateral Resistance Training Enhances and Preserves the Contralateral Knee Extensors Strength Gains After Detraining in Women: A Randomized Controlled Trial - Coratella, Giuseppe; Galas, Annalisa; Campa, Francesco; Pedrinolla, Anna; Schena, Federico; Venturelli, Massimo (Frontiers in Physiology, 2022)
The current randomized-controlled study investigated whether or not the inclusion of the eccentric phase in resistance training favours the contralateral strength gains after different unilateral protocols, and whether such gains are retained after detraining. Sixty healthy women were randomly assigned to a unilateral concentric-only (CONC), eccentric-only (ECC), concentric-eccentric (TRAD) volume-equated knee-extension training or control group (CON). The participants trained 2d/week for eight weeks and then did not train for further eight weeks. Knee-extensors isokinetic concentric, eccentric and isometric peak torque and vastus lateralis muscle thickness were assessed in the contralateral limb at baseline, post-training and post-detraining. At post-training, concentric peak torque increased in CONC [+9.2%, 95%CI (+6.2/+12.3), p<0.001, ES: 0.70, 95%CI (0.01/1.39)], ECC [+11.0%(+7.7/+14.2), p<0.001: ES: 0.66(0.09/1.23)] and TRAD [+8.5%(+5.7/+11.6), p<0.001, ES: 0.50(0.02/0.98)]. Eccentric peak torque increased in ECC in ECC [+15.0%(+11.4/+20.7), p<0.001, ES: 0.91(0.14/1.63)] and TRAD [+5.5%(+0.3/10.7), p=0.013, ES: 0.50(0.05/0.95)]. Isometric peak torque increased in ECC [+11.3(+5.8/16.8), p<0.001, ES: 0.52(0.10/0.94)] and TRAD [+8.6%(+3.4/+13.7), p<0.001, ES: 0.55(0.14/0.96)]. No change in eccentric and isometric peak torque occurred in CONC (p>0.05). Muscle thickness did not change in any group (p>0.05). At post-detraining, all groups preserved the contralateral strength gains observed at post-training (p<0.05). The findings showed that ECC and TRAD increased contralateral knee-extensors strength in concentric, eccentric and isometric modality, while CONC only increased concentric strength. The eccentric phase appears to amplify the cross-education effect, permitting a transfer in strength gaining towards multiple testing modalities. Both eccentric-based and traditional eccentric-concentric resistance protocols are recommended to increase the contralateral retention in strength gains after a detraining period.